A comparative performance analysis of Islamic and conventional banking: a case study of Pakistan - Ahmad, Altaf; Zakariyah, Habeebullah (Springer International Publishing, 2021)
The objective of this research is to critically evaluate the performance indicators which are used in previous studies and propose a comprehensive indicator to check the performance of selected Islamic and Conventional banks of Pakistan over the period of 2011–2016. The comprehensive indicator of performance is comprised of indicator of profitability, customer satisfaction and cost & revenue efficiency. Where the efficiencies measured using Stochastic Frontier Analysis, while overall indicator has been constructed using Principle Factor Analysis. This study provides ranking of selected banks based on the new indicator of performance and insights to what are possible determinants in conventional and Islamic banking system. This study then compared the determinants of performance such as Bank size, Operating efficiency, Management efficiency, Employee efficiency, and Funding cost between conventional and Islamic banks which are comparable in size. To compare the determinants of performance, regression analysis was applied. Feasible Generalized Least Square (FGLS) approach later used to compare the determinants of performance. Findings show that Meezan bank tops in revenue efficiency and Askari bank tops in cost efficiency. In overall performance comparison, Meezan bank tops accordingly. This study identifies Operating efficiency, Management efficiency, Employee efficiency, and Funding cost as important determinants of Pakistani banking sector.